Key for crossing the BBB with nanoparticles: the rational design - Lombardo, Sonia M.; Schneider, Marc; Türeli, Akif E.; Günday Türeli, Nazende (Beilstein Journal of Nanotechnology, 2020)
Central nervous system diseases are a heavy burden on society and health care systems. Hence, the delivery of drugs to the brain has gained more and more interest. The brain is protected by the blood–brain barrier (BBB), a selective barrier formed by the endothelial cells of the cerebral microvessels, which at the same time acts as a bottleneck for drug delivery by preventing the vast majority of drugs to reach the brain. To overcome this obstacle, drugs can be loaded inside nanoparticles that can carry the drug through the BBB. However, not all particles are able to cross the BBB and a multitude of factors needs to be taken into account when developing a carrier system for this purpose. Depending on the chosen pathway to cross the BBB, nanoparticle material, size and surface properties such as functionalization and charge should be tailored to fit the specific route of BBB crossing.
Keywords: gold nanoparticles (AuNPs); blood–brain barrier (BBB); drug delivery; liposomes; nanomedicine; polymeric nanoparticles; solid lipid nanoparticles; superparamagnetic iron oxide nanoparticles (SPIONs)

World Health Organization. The top 10 causes of death

(untitled) - Rajkovic, O.; Potjewyd, G.; Pinteaux, E. (Front. Neurol., 2018)

(untitled) - Abbott, N. J.; Rönnbäck, L.; Hansson, E. (Nat. Rev. Neurosci., 2006)

(untitled) - Sweeney, M. D.; Sagare, A. P.; Zlokovic, B. V. (Nat. Rev. Neurol., 2018)

(untitled) - Abbott, N. J.; Patabendige, A. A. K.; Dolman, D. E. M.; Yusof, S. R.; Begley, D. J. (Neurobiol. Dis., 2010)

(untitled) - Hawkins, B. T.; Davis, T. P. (Pharmacol. Rev., 2005)

(untitled) - Saraiva, C.; Praça, C.; Ferreira, R.; Santos, T.; Ferreira, L.; Bernardino, L. (J. Controlled Release, 2016)

(untitled) - Ballabh, P.; Braun, A.; Nedergaard, M. (Neurobiol. Dis., 2004)

(untitled) - Patel, M. M.; Goyal, B. R.; Bhadada, S. V.; Bhatt, J. S.; Amin, A. F. (CNS Drugs, 2009)

(untitled) - Chaichana, K. L.; Pinheiro, L.; Brem, H. (Ther. Delivery, 2015)

(untitled) - Mistry, A.; Stolnik, S.; Illum, L. (Int. J. Pharm., 2009)

(untitled) - Bourganis, V.; Kammona, O.; Alexopoulos, A.; Kiparissides, C. (Eur. J. Pharm. Biopharm., 2018)

(untitled) - Gänger, S.; Schindowski, K. (Pharmaceutics, 2018)

(untitled) - Erdő, F.; Bors, L. A.; Farkas, D.; Bajza, Á.; Gizurarson, S. (Brain Res. Bull., 2018)

(untitled) - Agrawal, M.; Saraf, S.; Saraf, S.; Antimisiaris, S. G.; Chougule, M. B.; Shoyele, S. A.; Alexander, A. (J. Controlled Release, 2018)

(untitled) - Pires, P. C.; Santos, A. O. (J. Controlled Release, 2018)

(untitled) - Lochhead, J. J.; Thorne, R. G. (Adv. Drug Delivery Rev., 2012)

The Blood-Brain and Other Neural Barriers: Reviews and Protocols - Blanchette, M.; Fortin, D. (Blood-Brain Barrier Disruption in the Treatment of Brain Tumors, 2011)

(untitled) - Etame, A. B.; Diaz, R. J.; O'Reilly, M. A.; Smith, C. A.; Mainprize, T. G.; Hynynen, K.; Rutka, J. T. (Nanomedicine (N. Y., NY, U. S.), 2012)

(untitled) - Bing, K. F.; Howles, G. P.; Qi, Y.; Palmeri, M. L.; Nightingale, K. R. (Ultrasound Med. Biol., 2009)

(untitled) - Posadas, I.; Monteagudo, S.; Ceña, V. (Nanomedicine (London, U. K.), 2016)

European Commission. Definition - Nanomaterials

Drug Delivery: Nanoparticles - Fattal, E.; Vauthier, C. (James Swarbrick, 2007)

(untitled) - Kreuter, J.; Alyautdin, R. N.; Kharkevich, D. A.; Ivanov, A. A. (Brain Res., 1995)

(untitled) - Kreuter, J. (Adv. Drug Delivery Rev., 2014)

(untitled) - Andrieux, K.; Couvreur, P. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2009)

(untitled) - Tapeinos, C.; Battaglini, M.; Ciofani, G. (J. Controlled Release, 2017)

(untitled) - Ulbrich, K.; Knobloch, T.; Kreuter, J. (J. Drug Targeting, 2011)

(untitled) - Aghaie, T.; Jazayeri, M. H.; Manian, M.; Khani, L.; Erfani, M.; Rezayi, M.; Ferns, G. A.; Avan, A. (J. Cell. Biochem., 2019)

(untitled) - Shevtsov, M. A.; Nikolaev, B. P.; Yakovleva, L. Y.; Marchenko, Y. Y.; Dobrodumov, A. V.; Mikhrina, A. L.; Martynova, M. G.; Bystrova, O. A.; Yakovenko, I. V.; Ischenko, A. M. (Int. J. Nanomed., 2014)

(untitled) - Sanchez-Covarrubias, L.; Slosky, L. M.; Thompson, B. J.; Davis, T. P.; Ronaldson, P. T. (Curr. Pharm. Des., 2014)

(untitled) - Banks, W. A.; Owen, J. B.; Erickson, M. A. (Pharmacol. Ther., 2012)

(untitled) - Boado, R. J.; Li, J. Y.; Nagaya, M.; Zhang, C.; Pardridge, W. M. (Proc. Natl. Acad. Sci. U. S. A., 1999)

Brain Targeted Drug Delivery System - Zhang, Z.; Zhan, C. (Receptor-Mediated Transportation through BBB, 2019)

(untitled) - Kim, R. B. (Drug Metab. Rev., 2002)

(untitled) - Mahringer, A.; Ott, M.; Reimold, I.; Reichel, V.; Fricker, G. (Curr. Pharm. Des., 2011)

(untitled) - Miller, D. S. (Trends Pharmacol. Sci., 2010)

Brain Targeted Drug Delivery System - Chen, R.; Zhao, X.; Hu, K. (Efflux Pump Inhibition to Enhance Brain Targeting Delivery, 2019)

(untitled) - Villaseñor, R.; Lampe, J.; Schwaninger, M.; Collin, L. (Cell. Mol. Life Sci., 2019)

(untitled) - Pulgar, V. (Front. Neurosci., 2019)

(untitled) - Jones, A. R.; Shusta, E. V. (Pharm. Res., 2007)

(untitled) - Lajoie, J. M.; Shusta, E. V. (Annu. Rev. Pharmacol. Toxicol., 2015)

Advances in Pharmacology - Preston, J. E.; Joan Abbott, N.; Begley, D. J. (Transcytosis of Macromolecules at the Blood–Brain Barrier, 2014)

(untitled) - Gao, H.; Yang, Z.; Zhang, S.; Pang, Z.; Jiang, X. (J. Drug Targeting, 2014)

(untitled) - Hervé, F.; Ghinea, N.; Scherrmann, J.-M. (AAPS J., 2008)

(untitled) - Lu, W. (Curr. Pharm. Biotechnol., 2012)

Brain Targeted Drug Delivery System - Zhu, X.; Jin, K.; Huang, Y.; Pang, Z. (Brain Drug Delivery by Adsorption-Mediated Transcytosis, 2019)

(untitled) - Bickel, U.; Yoshikawa, T.; Pardridge, W. M. (Adv. Drug Delivery Rev., 2001)

(untitled) - Kreuter, J.; Petrov, V. E.; Kharkevich, D. A.; Alyautdin, R. N. (J. Controlled Release, 1997)

(untitled) - Kreuter, J.; Ramge, P.; Petrov, V.; Hamm, S.; Gelperina, S. E.; Engelhardt, B.; Alyautdin, R.; von Briesen, H.; Begley, D. J. (Pharm. Res., 2003)

Plasmaproteinadsorption Als Möglicher Schlüsselfaktor Für Eine Kontrollierte Arzneistoffapplikation Mit Partikulären Trägern - Lück, M. (Freie Universität Berlin, 1997)

(untitled) - Kreuter, J.; Shamenkov, D.; Petrov, V.; Ramge, P.; Cychutek, K.; Koch-Brandt, C.; Alyautdin, R. (J. Drug Targeting, 2002)

(untitled) - Ambruosi, A.; Gelperina, S.; Khalansky, A.; Tanski, S.; Theisen, A.; Kreuter, J. (J. Microencapsulation, 2006)

(untitled) - Kreuter, J. (J. Nanosci. Nanotechnol., 2004)

(untitled) - Petri, B.; Bootz, A.; Khalansky, A.; Hekmatara, T.; Müller, R.; Uhl, R.; Kreuter, J.; Gelperina, S. (J. Controlled Release, 2007)

(untitled) - Gelperina, S.; Maksimenko, O.; Khalansky, A.; Vanchugova, L.; Shipulo, E.; Abbasova, K.; Berdiev, R.; Wohlfart, S.; Chepurnova, N.; Kreuter, J. (Eur. J. Pharm. Biopharm., 2010)

(untitled) - Tahara, K.; Miyazaki, Y.; Kawashima, Y.; Kreuter, J.; Yamamoto, H. (Eur. J. Pharm. Biopharm., 2011)

(untitled) - Ren, T.; Xu, N.; Cao, C.; Yuan, W.; Yu, X.; Chen, J.; Ren, J. (J. Biomater. Sci., Polym. Ed., 2009)

(untitled) - Raudszus, B.; Partikel, K.; Mulac, D.; Langer, K. (Mater. Today: Proc., 2017)

(untitled) - Chen, Y.-C.; Hsieh, W.-Y.; Lee, W.-F.; Zeng, D.-T. (J. Biomater. Appl., 2013)

(untitled) - Zensi, A.; Begley, D.; Pontikis, C.; Legros, C.; Mihoreanu, L.; Büchel, C.; Kreuter, J. (J. Drug Targeting, 2010)

(untitled) - Kreuter, J.; Hekmatara, T.; Dreis, S.; Vogel, T.; Gelperina, S.; Langer, K. (J. Controlled Release, 2007)

(untitled) - Kratzer, I.; Wernig, K.; Panzenboeck, U.; Bernhart, E.; Reicher, H.; Wronski, R.; Windisch, M.; Hammer, A.; Malle, E.; Zimmer, A.; Sattler, W. (J. Controlled Release, 2007)

(untitled) - Michaelis, K.; Hoffmann, M. M.; Dreis, S.; Herbert, E.; Alyautdin, R. N.; Michaelis, M.; Kreuter, J.; Langer, K. (J. Pharmacol. Exp. Ther., 2006)

(untitled) - Neves, A. R.; Queiroz, J. F.; Reis, S. (J. Nanobiotechnol., 2016)

(untitled) - Dal Magro, R.; Ornaghi, F.; Cambianica, I.; Beretta, S.; Re, F.; Musicanti, C.; Rigolio, R.; Donzelli, E.; Canta, A.; Ballarini, E.; Cavaletti, G.; Gasco, P.; et al. (J. Controlled Release, 2017)

(untitled) - Bana, L.; Minniti, S.; Salvati, E.; Sesana, S.; Zambelli, V.; Cagnotto, A.; Orlando, A.; Cazzaniga, E.; Zwart, R.; Scheper, W.; Masserini, M.; Re, F. (Nanomedicine (N. Y., NY, U. S.), 2014)

(untitled) - Xin, H.; Jiang, X.; Gu, J.; Sha, X.; Chen, L.; Law, K.; Chen, Y.; Wang, X.; Jiang, Y.; Fang, X. (Biomaterials, 2011)

(untitled) - Kadari, A.; Pooja, D.; Gora, R. H.; Gudem, S.; Kolapalli, V. R. M.; Kulhari, H.; Sistla, R. (Eur. J. Pharm. Biopharm., 2018)

(untitled) - Ruan, S.; Yuan, M.; Zhang, L.; Hu, G.; Chen, J.; Cun, X.; Zhang, Q.; Yang, Y.; He, Q.; Gao, H. (Biomaterials, 2015)

(untitled) - Velasco-Aguirre, C.; Morales-Zavala, F.; Salas-Huenuleo, E.; Gallardo-Toledo, E.; Andonie, O.; Muñoz, L.; Rojas, X.; Acosta, G.; Sánchez-Navarro, M.; Giralt, E.; Araya, E.; Albericio, F.; et al. (Nanomedicine (London, U. K.), 2017)

(untitled) - Chang, J.; Paillard, A.; Passirani, C.; Morille, M.; Benoit, J.-P.; Betbeder, D.; Garcion, E. (Pharm. Res., 2012)

(untitled) - Gupta, Y.; Jain, A.; Jain, S. K. (J. Pharm. Pharmacol., 2007)

(untitled) - Ulbrich, K.; Hekmatara, T.; Herbert, E.; Kreuter, J. (Eur. J. Pharm. Biopharm., 2009)

(untitled) - Cui, Y.; Xu, Q.; Chow, P. K.-H.; Wang, D.; Wang, C.-H. (Biomaterials, 2013)

(untitled) - Zhao, H.; Bao, X.-j.; Wang, R.-z.; Li, G.-l.; Gao, J.; Ma, S.-h.; Wei, J.-j.; Feng, M.; Zhao, Y.-j.; Ma, W.-b.; Yang, Y.; Li, Y.-n.; et al. (Hum. Gene Ther., 2011)

(untitled) - Chen, X.; Yuan, M.; Zhang, Q.; Ting Yang, Y.; Gao, H.; He, Q. (Curr. Pharm. Biotechnol., 2016)

(untitled) - Dixit, S.; Novak, T.; Miller, K.; Zhu, Y.; Kenney, M. E.; Broome, A.-M. (Nanoscale, 2015)

(untitled) - Praça, C.; Rai, A.; Santos, T.; Cristovão, A. C.; Pinho, S. L.; Cecchelli, R.; Dehouck, M.-P.; Bernardino, L.; Ferreira, L. S. (J. Controlled Release, 2018)

(untitled) - Aktaş, Y.; Yemisci, M.; Andrieux, K.; Gürsoy, R. N.; Alonso, M. J.; Fernandez-Megia, E.; Novoa-Carballal, R.; Quiñoá, E.; Riguera, R.; Sargon, M. F.; Çelik, H. H.; Demir, A. S.; et al. (Bioconjugate Chem., 2005)

(untitled) - Loureiro, J. A.; Gomes, B.; Fricker, G.; Coelho, M. A. N.; Rocha, S.; Pereira, M. C. (Colloids Surf., B, 2016)

(untitled) - Gu, J.; Al-Bayati, K.; Ho, E. A. (Drug Delivery Transl. Res., 2017)

(untitled) - Tang, X.; Liang, Y.; Zhu, Y.; Xie, C.; Yao, A.; Chen, L.; Jiang, Q.; Liu, T.; Wang, X.; Qian, Y.; Wei, J.; Ni, W.; et al. (Int. J. Nanomed., 2015)

(untitled) - Xia, C.-F.; Boado, R. J.; Zhang, Y.; Chu, C.; Pardridge, W. M. (J. Gene Med., 2008)

(untitled) - Mourtas, S.; Lazar, A. N.; Markoutsa, E.; Duyckaerts, C.; Antimisiaris, S. G. (Eur. J. Med. Chem., 2014)

(untitled) - Prades, R.; Guerrero, S.; Araya, E.; Molina, C.; Salas, E.; Zurita, E.; Selva, J.; Egea, G.; López-Iglesias, C.; Teixidó, M.; Kogan, M. J.; Giralt, E. (Biomaterials, 2012)

(untitled) - Hu, K.; Shi, Y.; Jiang, W.; Han, J.; Huang, S.; Jiang, X. (Int. J. Pharm., 2011)

(untitled) - Hu, K.; Li, J.; Shen, Y.; Lu, W.; Gao, X.; Zhang, Q.; Jiang, X. (J. Controlled Release, 2009)

(untitled) - Chen, H.; Tang, L.; Qin, Y.; Yin, Y.; Tang, J.; Tang, W.; Sun, X.; Zhang, Z.; Liu, J.; He, Q. (Eur. J. Pharm. Sci., 2010)

(untitled) - Meng, F.; Asghar, S.; Gao, S.; Su, Z.; Song, J.; Huo, M.; Meng, W.; Ping, Q.; Xiao, Y. (Colloids Surf., B, 2015)

(untitled) - Valenza, M.; Chen, J. Y.; Di Paolo, E.; Ruozi, B.; Belletti, D.; Ferrari Bardile, C.; Leoni, V.; Caccia, C.; Brilli, E.; Di Donato, S.; Boido, M. M.; Vercelli, A.; et al. (EMBO Mol. Med., 2015)

(untitled) - Tosi, G.; Vergoni, A. V.; Ruozi, B.; Bondioli, L.; Badiali, L.; Rivasi, F.; Costantino, L.; Forni, F.; Vandelli, M. A. (J. Controlled Release, 2010)

(untitled) - Costantino, L.; Gandolfi, F.; Tosi, G.; Rivasi, F.; Vandelli, M. A.; Forni, F. (J. Controlled Release, 2005)

(untitled) - Tosi, G.; Vilella, A.; Veratti, P.; Belletti, D.; Pederzoli, F.; Ruozi, B.; Vandelli, M. A.; Zoli, M.; Forni, F. (Mol. Pharmaceutics, 2015)

(untitled) - Shilo, M.; Motiei, M.; Hana, P.; Popovtzer, R. (Nanoscale, 2014)

(untitled) - Guerrero, S.; Araya, E.; Fiedler, J. L.; Arias, J. I.; Adura, C.; Albericio, F.; Giralt, E.; Arias, J. L.; Fernández, M. S.; Kogan, M. J. (Nanomedicine (London, U. K.), 2010)

(untitled) - Vio, V.; Riveros, A. L.; Tapia-Bustos, A.; Lespay-Rebolledo, C.; Perez-Lobos, R.; Muñoz, L.; Pismante, P.; Morales, P.; Araya, E.; Hassan, N.; Herrera-Marschitz, M.; Kogan, M. J. (Int. J. Nanomed., 2018)

(untitled) - Lockman, P. R.; Oyewumi, M. O.; Koziara, J. M.; Roder, K. E.; Mumper, R. J.; Allen, D. D. (J. Controlled Release, 2003)

(untitled) - Gaillard, P. J.; Appeldoorn, C. C. M.; Dorland, R.; van Kregten, J.; Manca, F.; Vugts, D. J.; Windhorst, B.; van Dongen, G. A. M. S.; de Vries, H. E.; Maussang, D.; van Tellingen, O. (PLoS One, 2014)

(untitled) - Lindqvist, A.; Rip, J.; Gaillard, P. J.; Björkman, S.; Hammarlund-Udenaes, M. (Mol. Pharmaceutics, 2013)

(untitled) - Li, J.; Zhang, C.; Li, J.; Fan, L.; Jiang, X.; Chen, J.; Pang, Z.; Zhang, Q. (Pharm. Res., 2013)

(untitled) - Mathew, A.; Fukuda, T.; Nagaoka, Y.; Hasumura, T.; Morimoto, H.; Yoshida, Y.; Maekawa, T.; Venugopal, K.; Kumar, D. S. (PLoS One, 2012)

(untitled) - Kim, J.-Y.; Choi, W. I.; Kim, Y. H.; Tae, G. (Biomaterials, 2013)

(untitled) - Chen, W.; Zhan, C.; Gu, B.; Meng, Q.; Wang, H.; Lu, W.; Hou, H. (J. Drug Targeting, 2011)

(untitled) - Lee, C.; Hwang, H. S.; Lee, S.; Kim, B.; Kim, J. O.; Oh, K. T.; Lee, E. S.; Choi, H.-G.; Youn, Y. S. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Rao, K. S.; Reddy, M. K.; Horning, J. L.; Labhasetwar, V. (Biomaterials, 2008)

(untitled) - Cheng, Y.; Dai, Q.; Morshed, R. A.; Fan, X.; Wegscheid, M. L.; Wainwright, D. A.; Han, Y.; Zhang, L.; Auffinger, B.; Tobias, A. L.; Rincón, E.; Thaci, B.; et al. (Small, 2014)

(untitled) - Xia, H.; Gao, X.; Gu, G.; Liu, Z.; Hu, Q.; Tu, Y.; Song, Q.; Yao, L.; Pang, Z.; Jiang, X.; Chen, J.; Chen, H. (Int. J. Pharm., 2012)

(untitled) - Tian, X.; Wei, F.; Wang, T.-x.; Wang, P.; Lin, X.; Wang, J.; Wang, D.; Ren, L. (Int. J. Nanomed., 2012)

(untitled) - Lu, W.; Tan, Y.-Z.; Hu, K.-L.; Jiang, X.-G. (Int. J. Pharm., 2005)

(untitled) - Parikh, T.; Bommana, M. M.; Squillante, E., III (Eur. J. Pharm. Biopharm., 2010)

(untitled) - Thöle, M.; Nobmann, S.; Huwyler, J.; Bartmann, A.; Fricker, G. (J. Drug Targeting, 2002)

(untitled) - Agarwal, A.; Majumder, S.; Agrawal, H.; Majumdar, S.; Agrawal, G. P. (Curr. Nanosci., 2011)

(untitled) - Wang, Z. H.; Wang, Z. Y.; Sun, C. S.; Wang, C. Y.; Jiang, T. Y.; Wang, S. L. (Biomaterials, 2010)

(untitled) - Wagner, S.; Zensi, A.; Wien, S. L.; Tschickardt, S. E.; Maier, W.; Vogel, T.; Worek, F.; Pietrzik, C. U.; Kreuter, J.; von Briesen, H. (PLoS One, 2012)

(untitled) - Panzenboeck, U.; Balazs, Z.; Sovic, A.; Hrzenjak, A.; Levak-Frank, S.; Wintersperger, A.; Malle, E.; Sattler, W. (J. Biol. Chem., 2002)

(untitled) - Moos, T.; Morgan, E. H. (J. Neurochem., 2001)

(untitled) - Paterson, J.; Webster, C. I. (Drug Discovery Today: Technol., 2016)

(untitled) - Niewoehner, J.; Bohrmann, B.; Collin, L.; Urich, E.; Sade, H.; Maier, P.; Rueger, P.; Stracke, J. O.; Lau, W.; Tissot, A. C.; Loetscher, H.; Ghosh, A.; et al. (Neuron, 2014)

(untitled) - Bien-Ly, N.; Yu, Y. J.; Bumbaca, D.; Elstrott, J.; Boswell, C. A.; Zhang, Y.; Luk, W.; Lu, Y.; Dennis, M. S.; Weimer, R. M.; Chung, I.; Watts, R. J. (J. Exp. Med., 2014)

(untitled) - Liu, J. K.; Teng, Q.; Garrity-Moses, M.; Federici, T.; Tanase, D.; Imperiale, M. J.; Boulis, N. M. (Neurobiol. Dis., 2005)

(untitled) - Bazan, J.; Całkosiński, I.; Gamian, A. (Hum. Vaccines Immunother., 2012)

(untitled) - Li, J.; Feng, L.; Fan, L.; Zha, Y.; Guo, L.; Zhang, Q.; Chen, J.; Pang, Z.; Wang, Y.; Jiang, X.; Yang, V. C.; Wen, L. (Biomaterials, 2011)

(untitled) - Kumar, P.; Wu, H.; McBride, J. L.; Jung, K.-E.; Hee Kim, M.; Davidson, B. L.; Kyung Lee, S.; Shankar, P.; Manjunath, N. (Nature, 2007)

(untitled) - Oswald, M.; Geissler, S.; Goepferich, A. (Mol. Pharmaceutics, 2017)

(untitled) - Silva, S.; Almeida, A. J.; Vale, N. (Biomolecules, 2019)

(untitled) - Farkhani, S. M.; Valizadeh, A.; Karami, H.; Mohammadi, S.; Sohrabi, N.; Badrzadeh, F. (Peptides, 2014)

(untitled) - Goulatis, L. I.; Shusta, E. V. (Curr. Opin. Struct. Biol., 2017)

(untitled) - Chen, Y.; Liu, L. (Adv. Drug Delivery Rev., 2012)

(untitled) - Gao, K.; Jiang, X. (Int. J. Pharm., 2006)

(untitled) - Oh, N.; Park, J.-H. (Int. J. Nanomed., 2014)

(untitled) - Zhang, S.; Li, J.; Lykotrafitis, G.; Bao, G.; Suresh, S. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Jo, D. H.; Kim, J. H.; Lee, T. G.; Kim, J. H. (Nanomedicine (N. Y., NY, U. S.), 2015)

(untitled) - De Jong, W. H.; Hagens, W. I.; Krystek, P.; Burger, M. C.; Sips, A. J. A. M.; Geertsma, R. E. (Biomaterials, 2008)

(untitled) - Sonavane, G.; Tomoda, K.; Makino, K. (Colloids Surf., B, 2008)

(untitled) - Khlebtsov, N.; Dykman, L. (Chem. Soc. Rev., 2011)

(untitled) - Nicholson, C.; Hrabětová, S. (Biophys. J., 2017)

(untitled) - Syková, E.; Nicholson, C. (Physiol. Rev., 2008)

(untitled) - Godin, A. G.; Varela, J. A.; Gao, Z.; Danné, N.; Dupuis, J. P.; Lounis, B.; Groc, L.; Cognet, L. (Nat. Nanotechnol., 2017)

(untitled) - Begley, D. J. (Sci. Transl. Med., 2012)

(untitled) - Lin, J.; Zhang, H.; Chen, Z.; Zheng, Y. (ACS Nano, 2010)

(untitled) - Goodman, C. M.; McCusker, C. D.; Yilmaz, T.; Rotello, V. M. (Bioconjugate Chem., 2004)

(untitled) - Lin, J.-Q.; Zheng, Y.-G.; Zhang, H.-W.; Chen, Z. (Langmuir, 2011)

(untitled) - Suk, J. S.; Xu, Q.; Kim, N.; Hanes, J.; Ensign, L. M. (Adv. Drug Delivery Rev., 2016)

(untitled) - Liu, Z.; Gao, X.; Kang, T.; Jiang, M.; Miao, D.; Gu, G.; Hu, Q.; Song, Q.; Yao, L.; Tu, Y.; Chen, H.; Jiang, X.; et al. (Bioconjugate Chem., 2013)

(untitled) - Guo, J.; Gao, X.; Su, L.; Xia, H.; Gu, G.; Pang, Z.; Jiang, X.; Yao, L.; Chen, J.; Chen, H. (Biomaterials, 2011)

(untitled) - Nance, E. A.; Woodworth, G. F.; Sailor, K. A.; Shih, T.-Y.; Xu, Q.; Swaminathan, G.; Xiang, D.; Eberhart, C.; Hanes, J. (Sci. Transl. Med., 2012)

(untitled) - Sulheim, E.; Baghirov, H.; von Haartman, E.; Bøe, A.; Åslund, A. K. O.; Mørch, Y.; de Lange Davies, C. (J. Nanobiotechnol., 2016)

(untitled) - Makadia, H. K.; Siegel, S. J. (Polymers (Basel, Switz.), 2011)

(untitled) - Filon, O.; Krivorotko, P.; Kobyakov, G.; Razjivina, V.; Maximenko, O.; Gelperina, S.; Kreuter, J. (J. Clin. Oncol., 2017)

(untitled) - Vieira, D. B.; Gamarra, L. F. (Int. J. Nanomed., 2016)

Doxorubicin-loaded Anti-EGFR-immunoliposomes (C225-ILs-dox) in High-grade Gliomas - Full Text View - ClinicalTrials.gov

(untitled) - Chen, C.; Duan, Z.; Yuan, Y.; Li, R.; Pang, L.; Liang, J.; Xu, X.; Wang, J. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Liu, Y.; Mei, L.; Xu, C.; Yu, Q.; Shi, K.; Zhang, L.; Wang, Y.; Zhang, Q.; Gao, H.; Zhang, Z.; He, Q. (Theranostics, 2016)

(untitled) - Cacciatore, I.; Ciulla, M.; Fornasari, E.; Marinelli, L.; Di Stefano, A. (Expert Opin. Drug Delivery, 2016)

(untitled) - Patel, M.; Souto, E. B.; Singh, K. K. (Expert Opin. Drug Delivery, 2013)

(untitled) - Fundarò, A.; Cavalli, R.; Bargoni, A.; Vighetto, D.; Zara, G. P.; Gasco, M. R. (Pharmacol. Res., 2000)

(untitled) - Zara, G. P.; Cavalli, R.; Bargoni, A.; Fundarò, A.; Vighetto, D.; Gasco, M. R. (J. Drug Targeting, 2002)

(untitled) - Zara, G. P.; Bargoni, A.; Cavalli, R.; Fundarò, A.; Vighetto, D.; Gasco, M. R. (J. Pharm. Sci., 2002)

(untitled) - Bargoni, A.; Cavalli, R.; Zara, G. P.; Fundarò, A.; Caputo, O.; Gasco, M. R. (Pharmacol. Res., 2001)

(untitled) - Kakkar, V.; Mishra, A. K.; Chuttani, K.; Kaur, I. P. (Int. J. Pharm., 2013)

(untitled) - Göppert, T. M.; Müller, R. H. (J. Drug Targeting, 2005)

(untitled) - Peira, E.; Marzola, P.; Podio, V.; Aime, S.; Sbarbati, A.; Gasco, M. R. (J. Drug Targeting, 2003)

(untitled) - Jain, K.; Sood, S.; Gowthamarajan, K. (Drug Delivery, 2015)

(untitled) - Gartziandia, O.; Herran, E.; Pedraz, J. L.; Carro, E.; Igartua, M.; Hernandez, R. M. (Colloids Surf., B, 2015)

(untitled) - Alam, M. I.; Baboota, S.; Ahuja, A.; Ali, M.; Ali, J.; Sahni, J. K.; Bhatnagar, A. (Int. J. Pharm., 2014)

(untitled) - Wavikar, P. R.; Vavia, P. R. (J. Liposome Res., 2015)

(untitled) - Attama, A. A. (Recent Pat. Drug Delivery Formulation, 2011)

(untitled) - Lim, W. M.; Rajinikanth, P. S.; Mallikarjun, C.; Kang, Y. B. (Int. J. Nanomed., 2014)

(untitled) - Song, S.; Mao, G.; Du, J.; Zhu, X. (Drug Delivery, 2016)

(untitled) - Tsai, M.-J.; Wu, P.-C.; Huang, Y.-B.; Chang, J.-S.; Lin, C.-L.; Tsai, Y.-H.; Fang, J.-Y. (Int. J. Pharm., 2012)

(untitled) - Khosa, A.; Reddi, S.; Saha, R. N. (Biomed. Pharmacother., 2018)

(untitled) - Zhang, X. (Cell Biochem. Biophys., 2015)

International Review of Neurobiology - Male, D.; Gromnicova, R.; McQuaid, C. (Gold Nanoparticles for Imaging and Drug Transport to the CNS, 2016)

(untitled) - Lasagna-Reeves, C.; Gonzalez-Romero, D.; Barria, M. A.; Olmedo, I.; Clos, A.; Sadagopa Ramanujam, V. M.; Urayama, A.; Vergara, L.; Kogan, M. J.; Soto, C. (Biochem. Biophys. Res. Commun., 2010)

(untitled) - Cheng, Y.; Meyers, J. D.; Agnes, R. S.; Doane, T. L.; Kenney, M. E.; Broome, A.-M.; Burda, C.; Basilion, J. P. (Small, 2011)

(untitled) - Burrows, N. D.; Lin, W.; Hinman, J. G.; Dennison, J. M.; Vartanian, A. M.; Abadeer, N. S.; Grzincic, E. M.; Jacob, L. M.; Li, J.; Murphy, C. J. (Langmuir, 2016)

(untitled) - Niidome, T.; Yamagata, M.; Okamoto, Y.; Akiyama, Y.; Takahashi, H.; Kawano, T.; Katayama, Y.; Niidome, Y. (J. Controlled Release, 2006)

(untitled) - An, L.; Wang, Y.; Tian, Q.; Yang, S. (Materials, 2017)

(untitled) - Parab, H. J.; Chen, H. M.; Lai, T.-C.; Huang, J. H.; Chen, P. H.; Liu, R.-S.; Hsiao, M.; Chen, C.-H.; Tsai, D.-P.; Hwu, Y.-K. (J. Phys. Chem. C, 2009)

(untitled) - Kolhar, P.; Anselmo, A. C.; Gupta, V.; Pant, K.; Prabhakarpandian, B.; Ruoslahti, E.; Mitragotri, S. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Laurent, S.; Forge, D.; Port, M.; Roch, A.; Robic, C.; Vander Elst, L.; Muller, R. N. (Chem. Rev., 2008)

(untitled) - Thakor, A. S.; Jokerst, J. V.; Ghanouni, P.; Campbell, J. L.; Mittra, E.; Gambhir, S. S. (J. Nucl. Med., 2016)

(untitled) - Neuwelt, A.; Sidhu, N.; Hu, C.-A. A.; Mlady, G.; Eberhardt, S. C.; Sillerud, L. O. (AJR, Am. J. Roentgenol., 2015)

(untitled) - Liu, D.-F.; Qian, C.; An, Y.-L.; Chang, D.; Ju, S.-H.; Teng, G.-J. (Nanoscale, 2014)

(untitled) - Kaluzova, M.; Bouras, A.; Machaidze, R.; Hadjipanayis, C. G. (Oncotarget, 2015)

(untitled) - Sillerud, L. O.; Solberg, N. O.; Chamberlain, R.; Orlando, R. A.; Heidrich, J. E.; Brown, D. C.; Brady, C. I.; Vander Jagt, T. A.; Garwood, M.; Vander Jagt, D. L. (J. Alzheimer's Dis., 2013)